Acute and long-term metabolic consequences of early developmental Bisphenol A exposure in zebrafish (Danio rerio). (October 2020) - Martínez, Rubén; Tu, Wenqing; Eng, Tyler; Allaire-Leung, Melissa; Piña, Benjamin; Navarro-Martín, Laia; Mennigen, Jan A.
Abstract: Bisphenol A (BPA) is an estrogenic contaminant linked to metabolic disruption. Developmental BPA exposure is of particular concern, as organizational effects may irreversibly disrupt metabolism at later life-stages. While BPA exposures in adult fish elicit metabolic perturbations similar to effects described in rodents, the metabolic effects of developmental BPA exposure in juvenile fish remain largely unknown. Following embryonic zebrafish exposure to BPA (0.1, 1 and 4 mg/L) and EE2 (10 ng/L) from 2 to 5 dpf, we assessed the metabolic phenotype in larvae (4–6 dpf) and juveniles (43–49 dpf) which had been divided into regular-fed and overfed groups at 29 dpf. Developmental BPA exposure in larvae dose-dependently reduced food-intake and locomotion and increased energy expenditure. Juveniles (29 dpf) exhibited a transient increase in body weight after developmental BPA exposure and persistent diet-dependent locomotion changes (43–49 dpf). At the molecular level, glucose and lipid metabolism-related transcript abundance clearly separated BPA exposed fish from controls and EE2 exposed fish at the larval stage, in juveniles on a regular diet and, to a lesser extent, in overfed juveniles. In general, the metabolic endpoints affected by BPA exposure were not mimicked by EE2 treatment. We conclude that developmental BPA exposure elicits acute metabolic effects in zebrafish larvae and fewer transient and persistent effects in juveniles and that these metabolic effects are largely independent of BPA's estrogenicity. Graphical abstract: Image 1 Highlights: Developmental BPA exposure results in acute, transient and long-term changes in zebrafish metabolism. Embryonic BPA exposure and juvenile nutritional challenge interact to affect locomotor behaviour. Most developmental BPA exposure effects are not mimicked by an estrogenic control.